ERK acts in parallel to PKCδ to mediate the connexin43-dependent potentiation of Runx2 activity by FGF2 in MC3T3 osteoblasts - Niger, Corinne (American Physiological Society, 2012)
The gap junction protein, connexin43 (Cx43), plays an important role in skeletal biology. Previously, we have shown that Cx43 can enhance the signaling and transcriptional response to fibroblast growth factor 2 (FGF2) in osteoblasts by increasing protein kinase C-δ (PKCδ) activation to affect Runx2 activity. In the present study, we show by luciferase reporter assays that the ERK signaling cascade acts in parallel to PKCδ to modulate Runx2 activity downstream of the Cx43-dependent amplification of FGF2 signaling. The PKCδ-independent activation of ERK by FGF2 was confirmed by Western blotting, as was the Cx43-dependent enhancement of ERK activation. Consistent with our prior observations for PKCδ, flow cytometry analyses show that Cx43 overexpression enhances the percentage of phospho-ERK-positive cells in response to FGF2, supporting the notion that shared signals among gap junction-coupled cells result in the enhanced response to FGF2. Western blots and luciferase reporter assays performed on osteoblasts cultured under low-density and high-density conditions revealed that cell-cell contacts are required for Cx43 to amplify ERK activation and gene transcription. Similarly, inhibition of gap junctional communication with the channel blocker 18β-glycyrrhetinic acid attenuates the Cx43-dependent enhancement of Runx2-transcriptional activity. In total, these data underscore the importance of cell-cell communication and activation of the ERK and PKCδ pathways in the coordination of the osteoblast response to FGF2 among populations of osteoblasts.